Cognitive Behavior Group Art Therapy to Reduce Students' Cyberbullying Behavior: Protocol Guide - Intan Kurniawati (Edupotensia, 2025)
Cyberbullying is a form of bullying conducted through electronic media. This behavior involves cruel actions intentionally directed at others by sending or posting harmful materials and engaging in other forms of social aggression. Many factors influence cyberbullying behavior, both from within the individual and from their environment. Cyberbullying can have serious effects on victims, such as stress, depression, and even the risk of suicide. Based on this, there is a need for services to reduce cyberbullying behavior. One service that can be offered is group counseling through Cognitive Behavior Art Therapy. This model integrates cognitive behavioral therapy with art therapy, providing students the opportunity to understand and manage their emotions and improve thought patterns that may contribute to cyberbullying behavior.